2007
DOI: 10.1088/0953-4075/40/14/004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of entanglement in the nonlinear optical coupler by homodyne-mediated feedback

Abstract: The enhancement of the intracavity entanglement of a nonlinear coupler via homodyne-mediated quantum feedback is investigated. It is found that the feedback can effectively enhance the squeezing, entanglement and purity of a two-mode field in the nonlinear coupler by appropriately choosing the quadrature angle at which the quantum feedback is introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…This method is limited by the strength of the optical nonlinearity employed, which is usually very weak, and is further reduced by the cavity damping. It has been shown that feedback can be used to increase the continuous-variable entanglement [290][291][292][293][294][295][296][297][298] generated in this way.…”
Section: Entanglement Creation and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is limited by the strength of the optical nonlinearity employed, which is usually very weak, and is further reduced by the cavity damping. It has been shown that feedback can be used to increase the continuous-variable entanglement [290][291][292][293][294][295][296][297][298] generated in this way.…”
Section: Entanglement Creation and Controlmentioning
confidence: 99%
“…A modified proposal in Refs. [291,292] is able to produce a pure steady-state two-mode entangled state by using two independent feedback loops to control the variances of X 1 − X 2 and Y 1 + Y 2 simultaneously.…”
Section: Entanglement Creation and Controlmentioning
confidence: 99%
“…We also note that an experimental generation system of the optical GHz-like and cluster-like quadripartite entangled states for continuous variables has been designed [25] . Recently, for the purpose of enhancement of squeezing and entanglement, based on feedback, the intracavity entanglement of a nonlinear couple via homodyne-mediated has been investigated [26] .C-V entanglement can be either produced by threelevel atom (s) [18,[27][28][29] or nonlinearly coupled waveguides intracavity [19,20,23,26] . A natural question arises whether we could integrate the three-level atom and nonlinearly coupled waveguides in the cavity together as a device that could enhance the C-V entanglement.…”
mentioning
confidence: 99%
“…We also note that an experimental generation system of the optical GHz-like and cluster-like quadripartite entangled states for continuous variables has been designed [25] . Recently, for the purpose of enhancement of squeezing and entanglement, based on feedback, the intracavity entanglement of a nonlinear couple via homodyne-mediated has been investigated [26] .…”
mentioning
confidence: 99%
See 1 more Smart Citation